A comprehensive review of the ecology and conservation status of spot-tailed earless lizards (Holbrookia lacerata and Holbrookia subcaudalis) - Rangel, E. Drake; Henke, Scott E.; Ayala, Ruby A.; Eversole, Cord B. (Frontiers in Amphibian and Reptile Science, 2024)
Spot-tailed Earless Lizards (STEL; Plateau STEL, Holbrookia lacerata; and Tamaulipan STEL, Holbrookia subcaudalis) are lizard species that are in decline both in number and distribution.As a result, this species has been considered for federal threatened status and a 90-day finding by the United States Fish and Wildlife Service stated that federal protection may be warranted. To date, a decision for Endangered Species Act listing for the Plateau STEL has been denied, but a judgement for the Tamaulipan STEL has not yet been decided. The requests to list STEL as a threatened species initiated numerous studies to investigate the status of both species and to add to the knowledge base of STEL. Though many studies have been conducted, much of the resulting information exists in gray literature (e.g., governmental reports, project summaries, etc.) that are not readily available or peer-reviewed. Herein, we consolidate the research results from scientific literature, governmental reports, and petitions to assist future researchers of STEL. We describe the natural history of STEL, their current taxonomy, conservation status, and discuss potential causes for their decline. Our goal is to provide the needed background knowledge for future researchers and policy makers.